MODAL SOSIAL KOMUNITAS YOGYAKARTA MENGAJAR DALAM PENYELENGGARAAN PENDIDIKAN NONFORMAL DI KAMPUNG GEMBLAKAN BAWAH KOTA YOGYAKARTA - Reza Falufi; Fransisca Winarni (NATAPRAJA, 2018)
The purpose of this research is to know and describe Social Capital of Yogyakarta Mengajar Community in the Implementation of Nonformal Education in Kampung Gemblakan Bawah Kota Yogyakarta. This research was a descriptive with qualitative approach research. The findings of the research showed that social capital of Yogyakarta Mengajar community in the implementation of nonformal education in Kampung Gemblakan Bawah Kota Yogyakarta is able to mobilize internal resources and build network outside the community. This can be seen through six indicators, namely: (1) the characteristic of social community that structured and systematic, (2) network and support from society and external community (3) collective action through reguler meetings with each other between fellow volunteers and community boards, (4) the trust established a strong, (6) the harmoniousness that exists because the volunteers consistently obey the values and norms prevailing in society.